2011
DOI: 10.1111/j.1537-2995.2010.03043.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of post donation information donors and comparison with appropriately deferred donors

Abstract: No previous studies have described the characteristics of PDI donors or examined how PDI donors are different from AD donors for the same deferral reasons. We found that PDIs are more likely in older, male donors with higher levels of education when compared to AD donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
12
1
1
Order By: Relevance
“…While our study did not show any significant association between failure to read predonation background material and noncompliance, we recognize the important role of donor education in improving risk disclosure as reported by researchers from other countries such as the United States . Effective delivery of predonation education material, using interactive ways of delivering information, and repeating important information in multiple formats are a few of the suggested measures for improving communication with potential donors, which is expected to improve compliance to the screening process overall.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…While our study did not show any significant association between failure to read predonation background material and noncompliance, we recognize the important role of donor education in improving risk disclosure as reported by researchers from other countries such as the United States . Effective delivery of predonation education material, using interactive ways of delivering information, and repeating important information in multiple formats are a few of the suggested measures for improving communication with potential donors, which is expected to improve compliance to the screening process overall.…”
Section: Discussioncontrasting
confidence: 52%
“…Finally, this study only included some of the high‐risk deferrals while noncompliance with other criteria (such as travel or incarceration) is not uncommon. According to a US study, the largest proportion of donors with postdonation information were those who did not disclose travel‐related (58.7%) information followed by medical (20.3%), high‐risk sexual behavior (10%), blood or disease exposure (6.22%), and high‐risk nonsexual behavior (includes IDU and incarceration; 4.76%) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we have seen, most of the currently estimated 0.4% of blood components discovered to be noncompliant after release come from donors who should have been deferred but were not. Donors who generated BPDs with postdonation information are more likely older, male, and more educated than deferred donors [72]. Table 7 lists several problems that have been identified with donor screening and deferral.…”
Section: Improving Donor Screening To Reduce Postdonation Problemsmentioning
confidence: 99%
“…Comparing appropriately deferred donors and PDI donors within the same broad deferral categories (travel, medical, blood disease or exposure, and high-risk–sexual and high-risk–nonsexual behaviors) it was found that PDI donors were more likely to be older, more educated, and male. 131 In a separate qualitative study, telephone interviews were conducted with appropriately deferred donors, PDI donors, and accepted donors just after their donation attempt or successful donation, respectively. Based on the interviews it was theorized that donors may need assistance from blood center staff on remembering dates for deferrable activities or, in some cases, in understanding specific items on the health history questionnaire.…”
Section: The Domestic Research Program– Major Findingsmentioning
confidence: 99%